2017
DOI: 10.1017/rdc.2017.129
|View full text |Cite
|
Sign up to set email alerts
|

Mortar Dating Methodology: Assessing Recurrent Issues and Needs for Further Research

Abstract: Absolute dating of mortars is crucial when trying to pin down construction phases of archaeological sites and historic stone buildings to a certain point in time or to confirm, but possibly also challenge, existing chronologies. To evaluate various sample preparation methods for radiocarbon (14C) dating of mortars as well as to compare different dating methods, i.e. 14C and optically stimulated luminescence (OSL), a mortar dating intercomparison study (MODIS) was set up, exploring existing limits and needs for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 20 publications
3
42
1
Order By: Relevance
“…They are formed during the drying up of salt lakes in summer. Sodium carbonates can be formed at the surface by absorption of carbon dioxide from the atmosphere or in the brine by combination of HCO 3 2− with Na 35 . Over the years the lake builds up a stratigraphy of deposits which are complicated by partial dissolution during the winter when the water rises again.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are formed during the drying up of salt lakes in summer. Sodium carbonates can be formed at the surface by absorption of carbon dioxide from the atmosphere or in the brine by combination of HCO 3 2− with Na 35 . Over the years the lake builds up a stratigraphy of deposits which are complicated by partial dissolution during the winter when the water rises again.…”
Section: Discussionmentioning
confidence: 99%
“…As early as the 1960s, 14 C dating was extended to building materials 1 . In particular, mortar which incorporates atmospheric carbon dioxide as it hardens, has been extensively studied and used to date churches and Roman buildings 2,3 .…”
mentioning
confidence: 99%
“…Previous studies have shown that a thorough mineralogical, petrological and geochemical characterization of the mortar sample is advised in order to plan a better sample preparation and dating strategy, or at least to have a basis for the correct interpretation of the results (Addis et al 2016(Addis et al , 2019Van Strydonck 2016;Marzaioli et al 2019). Hayen et al (2017) even stated that "Prescreening and characterization of the mortars should become a standard approach prior to the mortar dating in order to understand the failure risks of the dating process and to evaluate the data obtained".…”
Section: Figurementioning
confidence: 99%
“…For mortars and lime burials, the CO 2 fractions are obtained by the titration method or sequential dissolution (Van Strydonck et al 1982Hayen et al 2017). The powdered mortar sample is kept in suspension while 2 mL of 0.1 M HCl are added for the first four fractions then different amounts of~2.2 M HCl are added for the remaining fractions.…”
Section: Co 2 Extractionmentioning
confidence: 99%